KARAKTERISTIK SELAI BUAH NAGA (Hylocereus polyrhizus) MEMAR DENGAN FORMULASI PENAMBAHAN BUAH NANAS (Ananas comosus Merr.) - Abi Burhan; Nancy Eka Putri Manurung; Septi Hermialingga; Gemala Cahya (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2023)
The objective of this research is to know characteristics of breakable dragon fruit jam with adding pineapple puree. The research design used was a complete factorial random design. The cutting range with breakable area (A), with the type: A1 = 1 cm; A2 = 2 cm; and A3 = 3 cm. The second treatment is concentration of pineapple puree on dragon fruit jam (B), with the type: B1 = 0 % pineapple puree, B2 = 25 % pineapple puree, B3 = 50 % pineapple puree, B4 = 75 % pineapple puree, B5 = 100 % pineapple puree. The test parameters observed are water content, vitamin C content, crude fiber content, and total plate count. The results showed that adding pineapple pure can change dragon fruit jam characteristic. The cutting range 3 cm from breakable area is the safest dragon fruit to be raw material jam. The best treatment was obtained from A3B4 in concentrate pineapple puree is 75%.